Contribution of deep-earth fluids to the geothermal system: A case study in the Arxan volcanic region, northeastern China - Cui, Yueju; Sun, Fengxia; Liu, Lei; Xie, Chao; Li, Jing; Chen, Zhi; Li, Ying; Du, Jianguo (Frontiers in Earth Science, 2023)
Investigations of the hot spring water and gas in the volcanic region are involved in assessing geothermal resource and understanding groundwater circulation, volcano and earthquake activities. Origins of water and gas of the hot springs, lakes, river and rain in the Arxan volcanic region (ARV), northeastern (NE) China were investigated by conducting the field survey and geochemical analysis. The low electric conductivity (40 ~ 835 μS/cm) and low total dissolved solids (TDS, 23.83 ~ 540.00 mg/L) of the water samples indicate that they are fresh water. δ18O and δD values of the water samples range from -4.1‰ to -16.0‰ and from -61.3‰ to -119.9‰, respectively. Enrichment of heavy isotopes in the rain water and the crater lake waters was caused by evaporation. Component H2O of the water samples predominantly originated from the meteoric water, with less than 1vol% contributed by deep-Earth fluids. Ions in the rain sample were predominantly derived from sea salt and continental aerosol. Ions in the surface water samples had multiple origins (mineral dissolution, atmospheric and anthropogenic sources). While ions of the hot spring water were predominantly derived from both dissolution of rocks and deep-Earth fluids, the later contributed 73%~87% of Cl- and 86%~99% of Na+ to the hot spring waters. Gases from the hot springs were composed of more than 95% N2 and less than 5% of O2 and Ar with 3He/4He ratios of 0.14 ~ 1.17 RA (RA=1.4×10-6). Excess N2 and Ar, He and CO2 of the hot springs were mainly derived from both the crust and upper mantle. About 3% ~ 23% of total He in the bubbling gases from the crater lakers and hot springs is derived from the mantle, implying supplement of heat energy from the mantle to the geothermal systems. Significantly, about 12% of He dissolved in the Budonghe water is derived from the mantle, indicating that plenty of mantle-derived heat transported by deep-Earth fluids keeps the river water never frozen. Our results indicate that Cl, Na ions and 3He/4He ratio are the feasible geochemical indicators for source partitioning of geothermal fluids.